Estudo clínico e citogenético-molecular de pacientes portadores de cromossomos autossômicos em anel - Guilherme, Roberta dos Santos [UNIFESP] (2010)
Ring chromosomes usually result from breaks in their short and long arms followed by fusion of both ends causing genetic material loss. Nowadays with more sensible molecular techniques it is possible to better define the breakpoints and mechanism of ring chromosome formation. In this study we analyzed 13 patients with autosome ring chromosomes. We scored 300 metaphases from each patient lymphocyte cultures, using G banding and FISH with centromeric probes, in order to investigate the ring chromosome instability. A longitudinal study was done in patient VI with r(14) and in patient VII with r(15). They were investigated in two different periods with 19 years difference. Only the ring chromosomes 4 (case II) and 22 (cases XII and XIII) were considered stable since they present al lest 95% metaphases cells with only one monocentric ring, while the others were considered unstable. The longitudinal study showed that the r(14) and r(15) turned unstable during the period analyzed. In spite of the ring chromosomes instability had increased over the years, these patients did not present worse in clinical findings. Using the SNP-array technique, breakpoints and mechanisms of ring chromosome formation were determined in 12 patients. For the rings that we did not observe loss of genetic material in the short neither in the long arm MLPA and FISH techniques with subtelomeric and pantelomeric probes, respectively, were used. Thus, the patients´ karyotypes were determined as: 46,XY,r(3)(p26.1q29), 46,XX,r(4)(p16.3q35.2), 46,XY,r(10)(p15.3q26.2), 46,XX,r(10)(p15.3q26.13), 46,XY,r(13)(p13q31.1), 46,XY,r(14)(p13q32.33), 46,XX,r(15)(p13q26.2), 46,XY,r(18)(p11.32q22.2), 46,XX,r(18)(p11.32q21.33), 46,XX,r(18)(p11.21q23), 46,XY,r(22)(p13q13.33) and 46,XX,r(22)(p12q13.2). Different mechanisms were found to be involved in ring chromosome formation: from breaks in both chromosome arms, followed by end-to-end reunion (patients IV, VII-X and XII); from a break in one chromosome arm followed by fusion with the subtelomeric region of the other (patients I-II); from a break in one chromosome arm followed by fusion with the opposite telomeric region (patients III and IX); from fusion of two subtelomeric regions (patient VI); from telomere-telomere fusion (patient XI). Thus, the r(14) and one r(22) can be considered complete rings, since there was no loss of relevant genetic material. The r(13) showed a more complex mechanism of formation resulting in a deletion of 11.1 Mb concomitant with an interstitial duplication of 1.5 Mb with karyotype determined as 46,XY,r(13)(p13q33.1).arr13q33.1(101,543,509-103,001,462)x3,13q33.1q34(103,003,268-114,142,980)x1 dn. We concluded that the phenotypes of ring chromosome patients can be related with different factors, including gene haploinsufficiency, gene duplication and ring instability. Epigenetic factors related to gene expression changes due to the circular architecture of the ring chromosome must also be considered, since even patients with complete ring chromosomes can present associated phenotypic alterations, as observed in our patients with complete r(14) and r(22).